Why Are the Frequently Reported Delay Factors in Construction Projects Recurring?: A Qualitative Study - Kim, Jeonghyun; Bilbao, Pilar (International Journal of Sustainable Construction Engineering and Technology, 2023)
Since a construction project involves a huge amount of resources, delays in construction have an unfavorable impact on all stakeholders. Due to the large-scale, specialization, and complexity of construction projects, construction delays are reported globally. Previous quantitative studies mainly through questionnaires have focused on identifying delay factors. However, the identified delay factors show little difference regardless of time and region, thus, a more fundamental study on the root causes of the delay is needed. Therefore, this study intends to discuss in depth the causes of delay factors identified in previous studies from professionals’ point of view. According to the interview with the experts, schedule delays are caused by factors such as short initial construction periods, errors in design documents, and rework. The effect of construction delays includes not only work quality degradation and increased risk of workplace accidents, but also the professional ethical dilemma of managers. The experts mention that the construction delay can be alleviated with basic measures such as estimating spare construction period, reviewing design documents before work, and thorough quality control. This paper helps in understanding of the identified construction delays and can provide valuable insights in formulating effective strategies to avoid delays in construction projects.